GAMBARAN HISTOPATOLOGI HATI TIKUS WISTAR (Rattus norvegicus) PASCA PEMBERIAN MONOSODIUM GLUTAMAT - Angga Baskara; I.N. Arsana; N.K.A. Juliasih (JURNAL WIDYA BIOLOGI, 2019)
Monosodium glutamate (MSG) has been used very widely in the community as a food flavoring, and is thought to have a detrimental effect. This study aims to determine the effect of MSG on liver histopathology. 28 Wistar rats were used in this study. Rats were grouped into four groups: control (K), MSG-1 (MSG dose 1.5 mg / g bodyweight), MSG-2 (MSG dose 3.5 mg / g bw), and MSG-3 (MSG dose 4, 5 mg / g bw). MSG is given every day for 30 days. At the end of the treatment, the rat were euthanized and dissected for taking the liver. Histology preparation were made using the paraffin method and stained with Hematoxyclin Eosin (HE) staining. Kruskal Wallis and Mann Whitney test were used for statistical analysis. The results showed that the dose of MSG was 1.5; 3; and 4.5 mg / g bw causes liver damage with the same level of damage in the form of focused degeneration in one place. The higher the dose, the more degeneration of focused on one place which were found. Liver tissue damage scores in group K, MSG-1, MSG-2, and MSG-3 were 0; 0.4; 0.42857, and 0.45714. Conclusion, the administration of MGS has an effect on liver histopathology.